Poppy Ott and the galloping snail - Edwards, Leo, 1884-1944; Salg, Bert, 1881-1938 (Salt Lake City, UT : Project Gutenberg, 2023)
"Poppy Ott and the Galloping Snail" by Leo Edwards is a children's adventure novel written in the late 1920s. The book revolves around the exploits of Jerry Todd and his clever friend, Poppy Ott, as they embark on a hitchhiking adventure filled with mystery and humor. The story mixes elements of friendship, ingenuity, and the excitement of discovering quirky characters and unusual situations along their travels. The opening of the story introduces Jerry Todd as he struggles under the sun and laments about his lack of ice cream, while highlighting his camaraderie with Poppy Ott, who is described as a resourceful and fun-loving character. The two boys set off on a hitchhiking trip with high hopes and big dreams, only to find themselves in a desolate stretch of highway with no cars in sight. As evening draws near, they make plans to navigate the challenges ahead, leading them to encounter a mysterious farmer's mansion and hints of supernatural occurrences within it. The chapter sets a whimsical tone while establishing the central characters and hinting at the adventure filled with comedic mishaps and unexplainable phenomena they are about to embark on. (This is an automatically generated summary.)
Release date is 2023-08-08
David Edwards, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Humorous stories; Detective and mystery stories; Boys -- Juvenile fiction; Illinois -- Juvenile fiction